2023
DOI: 10.5267/j.uscm.2022.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Total quality management and its role in improving customer relations in Jordanian Islamic banks

Abstract: Total quality management (TQM) is a method of managing a bank. TQM, which is considered as a critical instrument, directs the strategy of developing work and increasing performance in order to generate profits through quality services and products. Therefore, this study aimed to examine the function of TQM in improving customer relations in Jordanian Islamic banks. Primary data was gathered by surveying 163 workers of Jordanian Islamic banks. A questionnaire was employed as the data-gathering technique. To do … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 26 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…As a result, there is increased interest in both theory and practice on the link between HRM and TQM as well as the relationship between these two viewpoints and corporate success (Al-Jarrah, Hailat, & Jarah, 2023). The management of human resources is a particularly challenging job both locally and globally.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As a result, there is increased interest in both theory and practice on the link between HRM and TQM as well as the relationship between these two viewpoints and corporate success (Al-Jarrah, Hailat, & Jarah, 2023). The management of human resources is a particularly challenging job both locally and globally.…”
Section: Literature Reviewmentioning
confidence: 99%
“…TQM has become an essential approach for organisations in various industries, including the banking sector (Al-Jarrah et al 2023;Alharth et al 2017). In recent years, there has been a push for superior quality in all industries, and the banking sector is no exception (Ayinaddis et al 2023;Marlapa 2020;Simwanza and Awolusi 2020).…”
Section: Total Quality Management In Bankingmentioning
confidence: 99%
“…This achievement stems from raising the satisfaction levels of internal employees by providing comprehensive and accurate information, enabling them to deliver improved services to external customers. Many studies have shown a high positive correlation between consumer satisfaction, improved performance, and TQM models (Al-Jarrah et al, 2023;Lepistö et al, 2022;Mehra & Ranganathan, 2008;Pattanayak et al, 2017;Terziovski, 2006). The strong association between total quality management and customer satisfaction enhances organizational performance.…”
Section: The Relationship Between Total Quality Management and Custom...mentioning
confidence: 99%
“…The strong association between total quality management and customer satisfaction enhances organizational performance. Studies by Pattanayak et al (2017) and Al-Jarrah et al (2023) in the banking domain have exposed a constructive impact of TQM on customer contentment. Drawing from these revelations, researchers put forward the initial hypothesis (H1) as follows: H1: Total Quality Management has a positive effect on Customer Satisfaction.…”
Section: The Relationship Between Total Quality Management and Custom...mentioning
confidence: 99%
See 1 more Smart Citation